PENINGKATAN PRODUKTIVITAS KELOMPOK WANITA TANI BANJAR PILING DALAM PEMBUATAN KRIPIK TALAS MENGGUNAKAN MESIN PEMOTONG UMBI - Astika, I M; Adnyana, I W B; Lokantara, I P; Dwijana, I GK (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Piling village is located in Tabanan Regency. Similar to the other areas in Tabanan regency, Piling village is also an agricultural area. The main products of agricultural are rice, fruits, vegetables and tubers. In Piling village there is a group of mothers who are members of Gapoktan and KWT who pursue the manufacture of chips from cassava. The survey and interviews result with the group, found that in the process of cutting / slicing requires a relatively long time because still using traditional tools, so that productivity is still low. Through this service program carried manufacture of production equipment are cutlery / slicer bulb so the productivity will increase and will be improve the welfare of society.